Vpliv stopnjevanega programa vadbe za moč na telesno sestavo in moč rok pri starejših ženskah - Zagorac, Urša (Šport (Ljubljana), 2023)
The first objective of the study was to examine the feasibility and effects of a progressive resistance training protocol on body composition and upper extremity strength in older adult women. The second objective was to determine if strength-related parameters and changes in body composition are correlated with the age of the participants. Strength was tested using a handgrip test and a unilateral biceps curl one repetition maximum (1RM) test as an indicators of upper extremity strength. Body composition was tested using bioimpedance. Sixty older adult women (age range 56 to 81 years), all residents occupants of the Črnomelj Health Centre, participated in an eight-week strength training protocol. A paired-samples t-test revealed a statistically significant improvement in left and right arm biceps curl results (p 0,05). The Pearson correlation coefficient showed no correlation between the changes in body composition and strength with the age of the participants (p > 0.05). We consider the progressive resistance training used in our study to be feasible and useful for improving upper extremity strength in older adult women, so it can be safely used in practice.
Keywords: moč; raziskave; starejše ženske; šport; telesna sestava; vadba